ChoreoGraphiComfort: Human Thermal Comfort in Vernacular Architectural Spaces - Baharin H.; Abd Manan M.S.; Abdul Shukor S.F.; Harun A.F.; Baharuddin N.; Ibrahim N.; Nohuddin P.N.E.; Bin Mastro M.H.; Jing H.T.; Ahmad Saffian K. (Association for Computing Machinery, 2024)
'ChoreoGraphiComfort' is inspired by a critical reflection on the organicity and corporeality that (e)merge in the thermal space of vernacular architecture. Abstracting the creative notions of choreography, graphics, and comfort, the artwork uses an ethnographic survey of living conditions in low-cost flats in Malaysia during the recent Covid-19 pandemic and an architectural representation of a 300-year-old traditional Malay house called Istana Puteri Bongsu. Centering the use on the issue of thermal comfort, a series of thermal images of the human body in various choreographed postures were filmed against the background of a traditional Malay house. The images were then fed into an AI platform to generate a new set of images that were morphed into each other. This creates a surrealist abstraction of what we term 'thermal choreography' that complicates the polemics of organic architecture and cultural wisdom in adapting human thermal comfort to the natural environment. 2023 Owner/Author.